Traumata on Screen: Cinematic Views from Southern Africa. Issue 4 (2nd October 2018) - Karam, Beschara; Kirby-Hirst, Mark
ABSTRACT: This special themed issue of Communicatio explores the profound transformation of the political, cultural and intellectual contours of Africa from the vantage point of African film and grounded within the theoretical and epistemological discourses of trauma studies, memory studies, postcolonial studies, and decolonial studies. The contributors are particularly interested in exploring the relational flows between African cinematic works and the social and imaginary circumstances of their production, engagement and representation. Through an explication of the screen and viewing cultures from Africa, this themed issue wishes to make three contributions. The first is to the already established but on-going scholarly work of trauma studies, but specifically from an African, cinematic vantage point. The second contribution is to the theoretical body of work on African cinema (and in this context, "cinematic" includes both film/television). And the last contribution is to the emerging view that culture is a "two-way street, " to put it colloquially: a reversal of the dominant "Western" direction of culture, with an emphasis on different tones of social values and contexts, that have been marginalised in mainstream popular culture discourses.